Dynamics of liquid–liquid flows in horizontal pipes using simultaneous two–line planar laser–induced fluorescence and particle velocimetry. (April 2018) - Ibarra, Roberto; Zadrazil, Ivan; Matar, Omar K.; Markides, Christos N.
Highlights: Simultaneous two–line (one per phase) PLIF–PI/TV applied to stratified oil–water pipe flows. Normalised mean velocity profiles collapse in the water phase but not in the oil phase. Laminar and turbulent velocity profiles modified by vertical velocity components. Turbulence intensity peaks close to the pipe wall and at the liquid–liquid interface. Mixing length model with the von Karman constant agrees reasonably well with data. Abstract: Experimental investigations are reported of stratified and stratified–wavy oil–water flows in horizontal pipes, based on the development and application of a novel simultaneous two–line (two–colour) technique combining planar laser–induced fluorescence with particle image/tracking velocimetry. This approach allows the study of fluid combinations with properties similar to those encountered in industrial field–applications in terms of density, viscosity, and interfacial tension, even though their refractive indices are not matched, and represents the first attempt to obtain detailed, spatiotemporally–resolved, full 2–D planar–field phase and velocity information in such flows. The flow conditions studied span mixture velocities in the range 0.3–0.6 m/s and low water–cuts up to 20%, corresponding to in situ (local) Reynolds numbers of 1750–3350 in the oil phase and 2860–11, 650 in the water phase, and covering the laminar/transitional and transitional/turbulent flow regimes for the oil and water phases, respectively. Detailed, spatiotemporally–resolved in situ phase and velocity data in a vertical plane aligned with the pipe centreline and extending across the entire height of the channel through both phases are analysed to provide statistical information on the interface heights, mean axial and radial (vertical) velocity components, (rms) velocity fluctuations, Reynolds stresses, and mixing lengths. The mean liquid–liquid interface height is mainly determined by the flow water cut and is relatively insensitive (up to 20% the highest water cut) to changes in the mixture velocity, although as the mixture velocity increases the interfacial profile transitions gradually from being relatively flat to containing higher amplitude waves. The mean velocity profiles show characteristics of both laminar and turbulent flow, and interesting interactions between the two co–flowing phases. In general, mean axial velocity profiles in the water phase collapse to some extent for a given water cut when normalised by the mixture velocity; conversely, profiles in the oil phase do not. Strong vertical velocity components can modify the shape of the axial velocity profiles. The axial turbulence intensity in the bulk of the water layer amounts to about 10% of the peak mean axial velocity in the studied flow conditions. In the oil phase, the axial turbulence intensity increases from low values to about 10% at the higher Reynolds numbers, perhaps due to transition from laminar to turbulent flow. The turbulence intensity showed peaks in regions of high shear, i.e., close to the pipe wall, and at the liquid–liquid interface. The development of the mixing length in the water phase, and also above the liquid–liquid interface in the oil phase, agrees reasonably well with predicted variations described by the von Karman constant. Finally, evidence of secondary flow structures both above and below the interface exists in the vertical velocity profiles, which is of interest to explore further.